The Urgency of Education for Humanity: A Comparison between Classical and Contemporary Islamic Philosophy of Education - Septia Sri Lestari; M. Sirozi (Journal La Sociale, 2025)
Education is a conscious and planned effort to create a pleasant learning and learning atmosphere so that students actively develop their potential. The philosophy of Islamic education is a concept of thinking about education that originates or is based on the teachings of the Islamic religion. The research used in this article is a library research approach or qualitative literature review. This method is carried out by analyzing or searching for objects such as books, articles, scientific journals, documents and other relevant literature to be used as references. This research discusses the urgency of education for humans and a comparison between classical and contemporary Islamic educational philosophy. Education is a basic human need. This is in line with education that will never end, so being an educated person is very important. Education has its own influence on life now and in the future. There are many influences resulting from education itself, education can also influence social strata in society, the higher a person's education, the better the views and things that a person will achieve. When Islamic education during the time of Rasulullah and Khulafa al-Rasyidin placed more emphasis on cultivating faith, sharia and morals as the basis for developing the people, classical Islamic education reached its peak during the reign of the Abbasids, which was characterized by openness to foreign culture and thought. The development of contemporary Islamic education with a breakdown of the thoughts of Abdurrahman Mas'ud, Hasan Langgulung, and Abdul Munir Mulkhan.